Filmes nanoestruturados para detecção do antígeno prostático específico - Graça, Juliana Santos (Universidade Federal de São Carlos, 2016)
In the present work, Layer-by-Layer films of Anti-PSA antibody in the absence and presence of DPPG liposomes were produced in order to study the detection of prostate specific antigen (PSA) by different characterization techniques. The free Anti-PSA antibody in solution and incorporated into liposome was characterized by UV-vis spectroscopy and Circular Dichroism (CD). In the first characterization, it was verified the main absorption bands of the antibody and a possible aggregation in the absence of the liposome. CD measurements indicated disordered structures of free antibody. However, its secondary structure (ß-Sheet) was maintained in the presence of liposomes. The film Layer- by-Layer of free Anti-PSA antibody and incorporated into DPPG liposomes was done alternating the antibody with different polycations, PAH (poly (allylamine hydrochloride)) and PEI (poly (ethyleneimine)). The films fabricate on quartz and gold sensors were characterized by UV-vis and SPR spectroscopy. These results proved the deposition of the materials on different substrates and the PEI was the best polyelectrolyte for immobilization of the antibody. Through the SPR measures it was simulated thickness and refractive index of the film bilayers. The PEI, PVS and Anti-PSA casting film and PEI/PVS and PEI/Anti-PSA LbL films were characterized by FTIR, it was observed through the bands of the spectra the interaction between the polyelectrolyte and found the deposition of antibody in the film. Acting as PSA detection unit, the (PEI/PVS)1/(PEI/Anti-PSA+DPPG)5 and (PEI/PVS)1/(PEI/Nati-PSA)5 films were characterized by cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS) and SPR and both systems were able to detect PSA at concentrations below 4 ng.mL-1 that is the normal concentration for a healthy individual.
Nanoestructured film from prostate specific antigen detection
Keywords: Materiais nanoestruturados; Nanostructured materials; Layer-by-Layer films; Anti-PSA antibody; PSA antigen; Liposome; Electrochemical detection; Filmes layer-by-layer; Anticorpo Anti-PSA livre e incorporado em lipossomos; Detecção do antígeno PSA por diferentes técnicas; Filmes camada por camada; Antígeno prostático específico (PSA); Lipossomos; Detecção eletroquímica; Detecção óptica; OUTROS